(N|WOL@CIQ GEOLOGI^ESKIH PROCESSOW W ISTORII zEMLI (B/s - (NqN[IN(B, (NaLEKSANDR lEONIDOWI^s ((NlENINGRA (B:s (NnAUKA(B. (NlENINGR(B. (NOTD(B-(NNIE(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 37-38s
Keywords: (NzEMLQs; (NrAZWITIEs